Examining foodwork and eating behaviors among heterosexual and gay male couples. (1st May 2022) - August, Kristin J.; Novak, Josh R.; Peak, Terry; Gast, Julie; Miyairi, Maya
Abstract: Objectives: Spouses play an important role in their partners' eating behaviors, including both promoting and impeding healthy eating. The division of foodwork in the relationship (i.e., if there is individual or shared responsibility for food roles) may vary as a function of gender or sexual orientation and may be important in understanding eating behaviors. Method: Using cross-sectional, dyadic data from 462 heterosexual and gay married couples ( N  = 921 individuals) residing in the United States, we accordingly sought to examine which partner was most responsible for two food roles, food shopping and meal preparation (Aim 1); whether these roles differed by gender (Aim 1a) and sexual orientation (Aim 1b); whether these food roles were related to the frequency of eating healthy and unhealthy foods (Aim 2); and whether these associations differed by gender (Aim 2a) and sexual orientation (Aim 2b). Results: We found that one individual was responsible for these roles in a majority of couples, although meal preparation was more likely to be shared in gay than in heterosexual couples. We also found that, in general, the person responsible for these food roles ate healthy more frequently compared to when their partner was responsible; findings for shared responsibility were more equivocal. These associations did not differ, however as a function of gender or sexual orientation. Conclusion: Our findings contribute to a further understanding of food dynamics among heterosexual and gay male couples and have important implications for health promotion and intervention efforts.